Modernization and Changes in Kiai-Santri Relations in Three Pesantrens in Java - Yon Machmudi (Islamica: Jurnal Studi Keislaman, 2021)
This study focuses on analyzing the changing role of kiai and his influences in pesantren. The decline of kiai’s authority in pesantren, besides being resulted from the changing role of kiai, is caused by social changes outside pesantren. As a result, kiai, who initially served as the agent of change and political reference, is now experiencing some challenges. To analyze such conditions, this study carefully uses the concept of authority and the patron-client relationship between kiai and santri. In this case, the research is carried out in three pesantrens in Java; Pesantren Cidahu Pandeglang, Pesantren Husnul Khotimah Kuningan, and Pesantren Darul Ulum Jombang. Pesantren that has transformed into a modern institution tends to be more resilient, but the influence of kiai toward his santris starts to decrease. Meanwhile, pesantren that remains as a traditional institution has reduced in number, but the influence of kiai toward the santris is still strong. Thus, this study shows that the power of kiai toward santri in modern pesantren has decreased due to modernization and social changes.